Analysis of Learning Motivation of Prospective Biology Teachers at Samawa University - Syafruddin, Syafruddin (Indonesian Journal of STEM Education, 2020)
The purpose of this research is to know the motivation to learn students S1 Biology Education FKIP University Samawa Sumbawa Besar, to know the factors that influence the motivation to learn students S1 Biology Education FKIP University Samawa Sumbawa Besar. This type of research is research on Mixed Methods Research Design. Student of Biology Education FKIP Samawa University is the population in this research while the research samples are taken throughout the students at every level which amounted to 27 students. Data collection techniques are done by questionnaire method in the form of learning Motivation questionnaire and interview technique. The data analysis used during the study was descriptive, percentage technique. Based on the results of the study showed that the motivation results learn S1 Students Biology Education FKIP University Samawa Sumbawa Besar amounted to 79.66% with a high category. Factors influencing the motivation to learn students S1 Biology Education FKIP University Samawa Sumbawa Besar is the motivation to learn intrinsic students who are courses taken/selected by students, a strong desire to continue education to a higher level. Factors that affect the motivation to learn an extrinsic student is a way lecturers teach in front of the class, the number of the semester credit system on each course, the characteristics of courses, the use of models, media and materials, and adequate facilities and infrastructure.